2022
DOI: 10.1007/s00234-022-03075-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of automated intracerebral hemorrhage volume measurement on non-contrast computed tomography: a Swedish Stroke Register cohort study

Abstract: Purpose Hematoma volume is the strongest predictor of patient outcome after intracerebral hemorrhage (ICH). The aim of this study was to validate novel fully automated software for quantification of ICH volume on non-contrast computed tomography (CT). Methods The population was defined from the Swedish Stroke Register (RS) and included all patients with an ICH diagnosis during 2016–2019 in Region Skåne. Hemorrhage volume on their initial head CT was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The most frequent locations for the ICH segmentations (in standard space) did not exceed 25% of the sample at any given site. This finding tends to align with work by others, who collectively reported on supratentorial locations, putamen, and thalamus as being common ICH locations, in addition to the cerebral hemispheres and ventricle locations ( 9 , 23 , 24 ). Future work is needed to characterize the locations of ICH in relation to radiological notes because there is renewed interest in location specific haematoma volume cut-offs in relation to outcomes ( 14 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most frequent locations for the ICH segmentations (in standard space) did not exceed 25% of the sample at any given site. This finding tends to align with work by others, who collectively reported on supratentorial locations, putamen, and thalamus as being common ICH locations, in addition to the cerebral hemispheres and ventricle locations ( 9 , 23 , 24 ). Future work is needed to characterize the locations of ICH in relation to radiological notes because there is renewed interest in location specific haematoma volume cut-offs in relation to outcomes ( 14 ).…”
Section: Discussionsupporting
confidence: 91%
“…The ROC analysis for the entire sample showed high performance metrics, while the performance metrics were lower for the suspected TBI site. Several other studies have reported on hemorrhage detection using CT scans ( 9 , 19 ) and these efforts used considerably larger sample sizes than the external CT cases for the current VIOLA-AI tool. It is intriguing that the VIOLA-AI tool achieved adequate classification performance for all samples, but the scores decreased when considering the low yield cases of consecutive mild TBI cases ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by our data demonstrating a correlation between CSF RBC count and both the modified Fisher score and the Hijdra ventricle score, the current state of the art to measure SAH volumes. Novel techniques to quantify intracranial blood volume are increasingly used [43][44][45], but do not necessarily improve predictive models for outcome [15]. In patients with intracerebral haemorrhage, artificial intelligence may help to rapidly quantify haematoma volume and the extension of perihaematomal oedema [46].…”
Section: Discussionmentioning
confidence: 99%
“… 11 In a Swedish stroke registry study, qER was found to have about 97% sensitivity in detecting non-traumatic ICH, and 95% of the false-negative ICHs were <1 mm in diameter. 28 In an unpublished study conducted for the purpose of regulatory submission, using 1320 NCCTH scans from multiple sites in the USA, the AUC was reported as over 97% for ICH, skull fracture, mass effect and midline shift. The sensitivity and specificity in detecting any one of the four abnormalities (ICH, skull fracture, mass effect, midline shift) were reported to be 98.53% (95% CI: 97.45% to 99.24%) and 91.22% (95% CI: 88.39% to 93.55%), respectively.…”
Section: Introductionmentioning
confidence: 99%